Tipologi dan kualitas sumber-sumber air di Pulau Yamdena dan Selaru, Maluku Tenggara Barat - Wulan Seizarwati; Heni Rengganis (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
Yamdena and Selaru Islands grouped in the cluster of Tanimbar Archipelago, West Southeast of Maluku. In this area, identified some water resources such as springs, dug wells, and rivers. Water quality study in this area is carried out in order to utilize water resources to support regional development of the small islands in Tanimbar Archipelago. The assessment of groundwater chemistry typology is performed to springs that potential to be developed, such as Wetemar, Wemomolin, Wesori, and Wetotote by using a classification method in Piper Trilinier Diagram. The assessment of water quality status and feasibility of utilization is performed to all type of water resources that has been identified and potential to be utilized. Physical and chemical parameters of water are obtained from direct measurement in field and laboratory testing. Analysis and evaluation results indicate that the typology of springs in Yamdena and Selaru Islands came from groundwater flow in the upper zone which was influenced by surface water. According to the laboratory testing results, almost water resources in Yamdena and Selaru Islands have not met yet the quality standard. The final results of this research are expected to be helpful for the further water utilization which is directed to make a sustainable utilization.